Preparation method of biomass hard carbon negative electrode material and application of biomass hard carbon negative electrode material in energy storage field
By pulverizing, screening, pickling, alkali washing and high-temperature calcining of biomass hard carbon materials, the problems of low efficiency and poor stability of biomass hard carbon materials in sodium ion batteries are solved, and the preparation and application of high-performance sodium ion battery hard carbon negative electrode materials are realized.
Patent Information
- Application Number
- CN202411759741.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
AI Technical Summary
The application of biomass hard carbon materials in sodium ion batteries is restricted by problems such as low efficiency, poor stability, and unstable sources for the first time, which restricts its large-scale industrial application.
By crushing and sieving the biomass raw materials, removing metal impurities and silicate impurities, and using high-temperature calcination and hydrofluoric acid hydrothermal treatment, a high-performance sodium ion battery hard carbon negative electrode material was prepared.
The reversible specific capacity, cycling performance and rate performance of hard carbon materials are improved, the electrochemical performance is improved, and the preparation cost and environmental pollution are reduced.
Smart Images

Figure CN119660733A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery electrode materials, and in particular to a method for preparing a biomass hard carbon negative electrode material and its application in the field of energy storage. Background Art
[0002] Sodium-ion batteries have great application potential in the field of large-scale energy storage due to their low price, wide sources, and green environmental protection. The preparation of high-performance, low-cost negative electrode materials is of great significance to the entire energy storage field. The negative electrode is an important component of sodium-ion batteries and plays a decisive role in the performance and cost of sodium-ion batteries. The negative electrode materials of sodium-ion batteries include carbon-based, sulfur-based, tin-based, metal alloys, metal oxides, and organic compounds. At present, carbon-based materials are the most promising negative electrode materials for industrialization, which mainly include graphitized carbon and non-graphitized carbon. Non-graphitized carbon is divided into soft carbon and hard carbon according to the difficulty of graphitization. Graphite has a regular layered structure, but because the interlayer spacing of graphite is small, Na + It is difficult to form a stable Na-C binary complex with graphite. After intercalation in graphite, only NaC 70 Compounds have low theoretical specific capacity, so existing commercial graphite is difficult to apply in sodium-ion batteries; compared with graphite, soft carbon has a relatively disordered chaotic layer structure, low crystallinity, and large interlayer spacing. However, when storing sodium in soft carbon materials through intercalation reactions, no obvious phase transition reaction occurs, there is no specific sodium storage voltage platform, and the voltage shows a slope characteristic with specific capacity changes, which also limits its practicality. The short-range ordered and long-range disordered graphite microcrystalline structure in hard carbon materials gives it more defect sites, micropores and sodium storage space. At the same time, the larger graphite microcrystalline interlayer spacing is conducive to the rapid diffusion of sodium ions.
[0003] Among them, biomass raw materials have the advantages of wide sources, low prices, strong controllability, good thermal stability, sufficient supply, and renewability, and are considered to be an ideal choice for large-scale production of hard carbon. However, biomass raw materials generally contain a certain amount of metal and non-metal impurities, which leads to a high ash content in hard carbon materials, low electronic conductivity, and impurities that are prone to side reactions with the electrolyte, which in turn affects the processability of hard carbon materials and the cycle stability, rate performance, and storage performance of sodium-ion batteries.
[0004] Although biomass hard carbon still has some defects, it still becomes one of the most promising negative electrode materials that is expected to achieve large-scale commercial production due to its advantages such as low price, wide source, and green environmental protection.
[0005] The low first coulombic efficiency, poor stability, and unstable sources of biomass carbon materials have seriously restricted the development and application of biomass carbon materials, greatly limiting the large-scale industrial application of biomass hard carbon materials in sodium ion batteries. Previous studies have mainly focused on improving the performance of carbon-based negative electrode materials while ignoring their preparation cost and safety; at the same time, the complex and cumbersome composition control method has significantly increased the difficulty of synthesizing the negative electrode, making it difficult to expand production; and previous work and research have mainly focused on the study of electrode materials, while ignoring the influence of electrode interface stability on electrode performance.
[0006] Invention patent CN117585663A discloses a biomass-based doped hard carbon negative electrode material and its preparation method. Cellulose and nickel foam are used as raw materials to construct hydrogel-wrapped nickel foam, and then an electrochemical oxidation method is used to prepare the hydrogel material. After calcination and etching, a high-strength hollow three-dimensional interwoven structure is obtained. Its reversible specific capacity reaches 350mAh / g and its initial efficiency reaches 90%. However, the synthesis method is complicated and it is questionable whether it can be commercialized on a large scale. Invention patent CN118684210A discloses a production process of biomass hard carbon for new energy batteries, in which the biomass is crushed and fed into a forward-turning blower, and then fed into a material density control device to control the process density, and then fed into a fixed carbonization furnace, where the capacity of the biomass in the fixed carbonization furnace is detected by a level meter, and ignited when the biomass reaches a set capacity, so that the biomass is heated to a set temperature for carbonization, and finally the roller material control device feeds the carbonized hard carbon precursor into a reverse-turning blower, where a non-contact cooling screw machine cools the hard carbon precursor to room temperature and transports it to a closed storage tank for storage. However, the implementation steps of this invention patent are cumbersome, require high manpower, consume a lot of energy, and cannot be fully commercialized on a large scale.
[0007] Based on the above problems, the purpose of the present invention is to seek a simple, efficient, green, environmentally friendly and low-cost method to prepare high-performance biomass hard carbon negative electrode materials, and to evaluate the performance of the prepared hard carbon negative electrode materials and analyze the electrochemical properties of the materials. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a sodium ion battery hard carbon negative electrode material and its preparation method and application. The present invention uses widely available and renewable biomass as raw materials, crushes and processes the biomass precursor powder by a crusher, screens out obviously large particles, carbonizes at low temperature, and pickles it to obtain a biomass precursor powder that basically does not contain metal impurities; then the obtained biomass precursor powder is immersed in an alkaline solution to remove silicate impurities therein to obtain a pretreated biomass precursor powder, and then the pretreated biomass precursor powder is calcined at high temperature to prepare a sodium ion battery hard carbon negative electrode material. The uniformity of the biomass precursor particles can be ensured by crushing and screening, and the influence of excessively large particles on subsequent experimental steps can be avoided, thereby improving the electrochemical properties of the hard carbon material; the metal impurities insoluble in water in the precursor or contained on the surface of the raw material itself are removed by pickling, and the influence of impurities on the battery is reduced; the residual carbon rate of the raw material can be increased by two-step high-temperature calcination; the battery performance finally prepared has the characteristics of high first coulomb efficiency, high low-pressure platform specific capacity, excellent cycle performance and rate performance.
[0009] The present invention is achieved through the following technical solutions:
[0010] The first object of the present invention is to provide a method for preparing a biomass hard carbon negative electrode material, comprising the following steps:
[0011] (1) pretreating, crushing and pre-carbonizing the biomass raw material to obtain a pre-carbonized material;
[0012] (2) mixing and stirring the pre-carbonized material obtained in step (1) with an acidic solution, washing and drying to obtain an acid-treated hard carbon material;
[0013] (3) immersing the acid-treated hard carbon material obtained in step (2) in an alkaline solution, heating and stirring, washing and drying to obtain an alkali-treated hard carbon material;
[0014] (4) mixing the alkali-treated hard carbon material obtained in step (3) with a pore-forming agent, ball milling, solid-liquid separation, and high-temperature carbonization and grinding of the obtained solid phase to obtain a powder sample;
[0015] (5) Mixing the powder sample obtained in step (4) with hydrofluoric acid and subjecting it to hydrothermal treatment to obtain a biomass hard carbon negative electrode material.
[0016] In one embodiment of the present invention, in step (1), the pretreatment conditions are:
[0017] The biomass raw material is immersed in deionized water for ultrasonic washing for 10-30 minutes to remove dust on the surface of the silkworm litter, centrifuged at 3000r / min-8000r / min for 3min-5min to remove excess deionized water, and then dried at 60-80°C.
[0018] In one embodiment of the present invention, in step (1), the pre-carbonization treatment conditions are: carbonization at 200° C.-400° C. for 1 h-12 h;
[0019] And / or, the biomass raw material is silkworm litter.
[0020] In one embodiment of the present invention, in step (2), the acid in the acidic solution is one or more of hydrochloric acid, nitric acid and sulfuric acid;
[0021] And / or, the concentration of the acidic solution is 0.1 mol / L-3 mol / L.
[0022] In one embodiment of the present invention, in step (3), the alkali in the alkaline solution is potassium hydroxide and / or sodium hydroxide;
[0023] And / or, in step (3), the heating conditions are: heating at 60°C-90°C for 3h-8h.
[0024] In one embodiment of the present invention, in step (4), the pore-forming agent is zinc chloride and / or potassium hydroxide;
[0025] And / or, the mass ratio of the alkali-treated hard carbon material to the pore-forming agent is 3:1-10:1.
[0026] In one embodiment of the present invention, in step (4), the material ratio of the ball mill is 4-10:1;
[0027] And / or, the rotation speed of the ball mill is 300r / min-600r / min;
[0028] And / or, the ball milling time is 3h-8h.
[0029] In one embodiment of the present invention, in step (4), the temperature of the high temperature carbonization is 1200° C.-1400° C.;
[0030] And / or, the heating rate of the high temperature carbonization is 2°C / min-10°C / min;
[0031] And / or, the high temperature carbonization holding time is 2h-6h;
[0032] And / or, the high temperature carbonization is carried out under an inert atmosphere;
[0033] And / or, the conditions of the hydrothermal treatment are: 80°C-200°C for 10h-18h.
[0034] The second object of the present invention is to provide a biomass hard carbon negative electrode material prepared by the preparation method.
[0035] The third object of the present invention is to provide the application of the biomass hard carbon negative electrode material in the field of energy storage.
[0036] The fourth object of the present invention is to provide a sodium ion battery using the biomass hard carbon negative electrode material as the negative electrode material.
[0037] The present invention uses an acidic solution to remove metal impurities; an alkaline solution to remove silicate impurities; potassium hydroxide or zinc chloride is used as a pore-forming agent to increase the active sites of the material and improve the capacity. The acidic and alkaline waste liquids obtained by the acidic and alkaline treatments can be neutralized to reduce pollution to the environment. In addition, the present invention uses HF hydrothermal reaction to dope the material with F elements, and the inorganic-rich solid electrolyte interface (SEI) has higher ionic conductivity and stability, thereby having excellent long-cycle stability.
[0038] The above technical solution of the present invention has the following advantages compared with the prior art:
[0039] First, good processability: Biomass materials usually contain impurities. If these impurities are not removed, they will have a significant adverse effect on the subsequent electrode production. The acid-treated material of the present invention can effectively remove metal ion impurities and reduce the ash content of the material, which has a good effect in the subsequent coating process.
[0040] Second, high reversible specific capacity: After acid and alkali treatment, the material has basically removed the impurities contained in the material. After adding the pore-forming agent, a certain proportion of pores will be left inside the material. Then, after high-temperature carbonization, some larger pores will collapse and form closed pores. This makes the material have abundant active sites, which is conducive to the storage of sodium ions, thereby improving the reversible specific capacity of the material.
[0041] Third, improve cycle stability: hard carbon materials themselves have a large interlayer spacing, which is conducive to the embedding and extraction of sodium ions. Since fluorine atoms have a high electronegativity, after being inserted into the interlayer of hard carbon materials, the interlayer spacing of hard carbon materials can be further increased due to mutual repulsion. The increase in interlayer spacing is conducive to the rapid movement of ions, thereby improving the electrochemical performance of the battery. In addition, fluorine-doped hard carbon materials can provide more ion embedding sites while maintaining structural stability, thereby improving the battery's cycle performance and fast charging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0043] Figure 1This is a charge and discharge cycle test of the sodium ion battery electrode prepared in Example 1 of the present invention;
[0044] Figure 2 This is a charge and discharge cycle test of the sodium ion battery electrode prepared in Comparative Example 1 of the present invention;
[0045] Figure 3 This is a charge and discharge cycle test of the sodium ion battery electrode prepared in Comparative Example 2 of the present invention;
[0046] Figure 4 This is a charge and discharge cycle test of the sodium ion battery electrode prepared in Comparative Example 4 of the present invention;
[0047] Figure 5 This is a charge and discharge cycle test of the sodium ion battery electrode prepared in Comparative Example 5 of the present invention;
[0048] Figure 6 This is a charge and discharge cycle test of the sodium ion battery electrode prepared in Comparative Example 6 of the present invention;
[0049] Figure 7 This is a charge and discharge cycle test of the sodium ion battery electrode prepared in Comparative Example 7 of the present invention;
[0050] Figure 8 This is the rate test of the sodium ion battery electrode prepared in Example 1 of the present invention;
[0051] Fig. 9 This is the rate test of the sodium ion battery electrode prepared in Comparative Example 2 of the present invention;
[0052] Fig.10 This is the XRD test performed on the material prepared in Example 1 of the present invention;
[0053] Fig.11 This is an XRD test conducted on the material prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0054] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0055] In order to overcome the shortcomings of low specific capacity, low first coulombic efficiency, poor rate performance and cycle stability of biomass hard carbon materials in existing sodium ion batteries, the present invention provides a method for preparing biomass hard carbon negative electrode materials with pore-forming agents and element doping, which can effectively improve the reversible specific capacity of the hard carbon material, improve the rate performance and cycle stability of the material, and thus improve the electrochemical properties of the hard carbon negative electrode material.
[0056] The specific preparation steps are as follows:
[0057] S1. Pre-carbonization: The biomass raw material is crushed by a crusher, washed with deionized water, pre-carbonized, and crushed to obtain a hard carbon precursor material;
[0058] S2, pickling and impurity removal (using HCl, HNO 3、 H2SO4): mixing the precursor material obtained in step S1 with the diluted acid solution to obtain an acid-treated carbon material;
[0059] S3, alkali washing, impurity removal and pore formation (using one or more of KOH, NaOH, ZnCl2): the acid-treated carbon material obtained in step S2 is washed with water, then mixed with an alkali solution and reacted at a controlled temperature, followed by water washing and drying to obtain an alkali-treated carbon material;
[0060] S4, mixing the material obtained in S3 and the pore-forming agent in a certain proportion, transferring the mixture into a ball mill, and then mechanically mixing the mixture using a planetary ball mill, and then centrifuging the mixture and drying it in an oven;
[0061] S5, high temperature carbonization: the carbon material obtained in step S4 is subjected to high temperature carbonization under a protective gas to obtain a sodium ion battery negative electrode biomass hard carbon material.
[0062] Furthermore, the preparation method of the sodium ion battery hard carbon negative electrode material comprises the following specific steps:
[0063] Step 1: In an air atmosphere, keep the silkworm excrement biomass particles at 200℃-400℃ for 1h-12h, and naturally cool to room temperature to obtain a pre-carbonized product; the method for obtaining the biomass powder is: immerse the silkworm excrement biomass in a 500mL beaker containing deionized water for ultrasonic washing for 10-30min to remove dust on the surface of the silkworm excrement, use a centrifuge at 3000r / min-8000r / min, 3min-5min to remove excess deionized water, put it in an oven at 60℃-80℃ for drying, and then use a crusher to crush the dried material into fine powder, sieve it, and obtain biomass powder. Then put it into a tubular furnace for high-temperature carbonization treatment, the carbonization temperature is 200℃-400℃, the duration is 1h-12h, and it is naturally cooled to room temperature to obtain a pre-carbonized material.
[0064] Step 2: Mix the above pre-carbonized material and the diluted acid solution, stir with a magnetic stirrer for 1h-12h, the speed is 100r / min-1000r / min, the acid solution is one or more of hydrochloric acid, nitric acid or sulfuric acid, the concentration after dilution is 0.1-3mol / L, transfer it to a suction filter for suction filtration (the purpose is to wash away excess acid) and wash to neutrality (PH=7), then put it in an oven for drying, the oven temperature is 40℃-80℃, the insulation time is 3h-8h, and the hard carbon material with metal impurities removed can be obtained. .
[0065] Step 3: Immerse the powder obtained in step 2 in an alkaline solution, place the alkaline solution in a 500mL beaker, heat and stir, the alkaline solution is one or more of potassium hydroxide or sodium hydroxide solution, the heating temperature is 60℃-90℃, the heating time is 3h-8h, magnetic stirring is 1h-12h, transfer it to a suction filter for suction filtration (the purpose is to wash away excess alkali) and wash to neutrality (PH=7), put the obtained powder into an oven for drying, the oven temperature is 60℃-80℃, the insulation time is 3h-8h, and the acid-base waste liquid left in step 2 and step 3 is neutralized. The alkaline solution is one or a mixed solution of NaOH and KOH. Wash to neutrality: wash with water and anhydrous ethanol respectively.
[0066] Step 4: The powder obtained in step 3 is mixed with a pore-forming agent (zinc chloride or potassium hydroxide) in a ratio of 3:1-10:1 (specifically 3:1, 5:1 or 10:1), and placed in a ball mill for ball milling. The material ratio is 4-10:1 (i.e., the ratio of ball milling beads to materials). An ethanol solution is added as a solvent. The speed of the ball mill is 300r / min-600r / min, and the duration is 3h-8h. Then, the material is placed in a centrifuge tube for solid-liquid separation at a speed of 3000r / min-80 00r / min, duration is 3min-8min, put it in an oven for drying, the oven temperature is 60℃-80℃, the insulation time is 3h-8h, then put it in a crucible for high-temperature carbonization, the high temperature is 1200℃-1400℃, the heating rate is 2℃ / min-10℃ / min, the insulation time is 2h-6h, naturally cool to room temperature, take it out and put it into a mortar for grinding until there are no large particles, wash and dry (put it in an oven at 60℃-80℃, the insulation time is 6h-8h) for standby use.
[0067] Step 5: Mix the powder sample obtained in step 4 with 5-30 ml of hydrofluoric acid in the inner liner of a reactor (made of polytetrafluoroethylene, which does not react with hydrofluoric acid), and place it in the reactor for hydrothermal treatment (for the purpose of doping the F element). The conditions of the hydrothermal treatment are: keep warm at 80°C-200°C for 10h-18h, then cool naturally, remove excess HF, wash the material to neutrality, and place it in an oven for drying (in an oven at 60°C-80°C, the insulation time is 6h-8h).
[0068] Step six: Mix the final powder with the conductive agent and the binder in a certain proportion to prepare the electrode, use aluminum foil or copper foil as the current collector, then use a coating machine to coat it, put it in a vacuum drying oven for drying (vacuum and the temperature is 60℃-100℃, and the insulation time is 8h-12h), and use a cutting machine to cut out the electrode with a diameter of 10mm-15mm; assemble the button battery in a glove box with an oxygen / water content of less than 0.01ppm, assemble the button battery with sodium metal as the counter electrode, and use the blue electric system to test the cycle performance and rate performance of the installed electrode.
[0069] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0070] Example 1
[0071] This embodiment provides a method for preparing a hard carbon negative electrode material for a sodium ion battery, which specifically includes the following steps:
[0072] S1: Select 15g of biomass raw material with uniform particle size - silkworm sand, use deionized water to perform ultrasonic cleaning for multiple times (cleaning time is 15min) to remove dust and other leaf impurities on the surface of the material to avoid affecting the subsequent experimental results, and then put it into an 80℃ oven for drying for 10h; put the dried material into a crusher to crush it into fine powder, and further select the material through a 1500-mesh sieve. Its advantage is that it is convenient for controlling the density of biomass raw materials during pre-carbonization, and can achieve uniform carbonization of biomass materials; take some of the sieved materials and put them into a crucible, and put them into a tubular furnace with a maximum sintering temperature of 1200℃ for low-temperature carbonization at 300℃, with a heating rate of 5℃ / min and a holding time of 2h. The protective gas is nitrogen or argon.
[0073] S2: Grind the carbonized material in a mortar for 30 minutes until there are no obvious particles. Immerse it in 1M HCl and place it on a stirring table and stir it at 700r / min for 8 hours to make the material and the acid solution mix more evenly. Then use a vacuum filter to filter the acid solution for 1 hour, use PH test paper to test the final mixed solution, compare the color change, and ensure that there is no acid solution residue. Then use ethanol to wash the material several times, and finally put it in an oven at 80°C to dry for 10 hours.
[0074] S3: The final powder obtained from S2 is immersed in a 3M NaOH solution, and then placed in an oil bath and heated and stirred at a speed of 300 r / min and a temperature of 60°C for 2 hours to remove silicate impurities contained in the material. Then, the alkaline solution is filtered with a vacuum filter for 1 hour, and the final mixed solution is tested with pH test paper to compare the color changes to ensure that there is no alkaline solution remaining. The material is then washed several times with ethanol; then placed in an oven at 80°C for drying for 10 hours, and the acid and alkaline waste liquids remaining in S2 and S3 are neutralized. In addition, the sodium ions in NaOH are also beneficial to the final performance of the material.
[0075] S4: The final product of step S3 is mixed with zinc chloride in a mass ratio of 3:1 and ground until there are no obvious large particles, and the mixture is placed in a ball mill (wet ball milling, adding a certain amount of deionized water or ethanol), the material ratio is 10:1 (i.e., the ratio of ball mill beads to materials), ethanol solution or deionized water is added as a solvent, the speed of the ball mill is 400r / min, and the duration is 6h. Then, the material is placed in a centrifuge tube for solid-liquid separation, the speed is 5000r / min, the duration is 3min, and centrifugation is performed multiple times until the supernatant has no obvious color change, and the material is placed in an oven for drying, the oven temperature is 80°C, and the insulation time is 8h.
[0076] S5: Transfer the material obtained in S4 to a polytetrafluoroethylene liner, add 10 mL HF, place the liner in a hydrothermal reactor, tighten the reactor, and then place it in a 160°C forced air drying oven for 12 hours. After cooling to room temperature, open it, pour out excess HF, and then use a vacuum filter to treat the material to remove residual acid on the surface of the material, place it in an 80°C oven, and dry it for 8 hours.
[0077] S6: The final material obtained in S5 is moved into a crucible for high-temperature carbonization (nitrogen or argon is introduced for 30 minutes before sintering to exhaust the air inside the corundum tube to avoid the influence of air on the experimental results. The heating rate is 5°C / min, from 30°C to 1300°C, the insulation time is 2h, and argon inert gas is introduced), and it is allowed to cool naturally to room temperature. Take it out, grind it in a mortar for 60 minutes until there are no obvious particles to obtain the sodium ion battery hard carbon negative electrode material, put it into a glass bottle and put it into an oven at 80°C for use.
[0078] This embodiment also provides a method for preparing a sodium ion battery electrode, comprising the following steps:
[0079] According to the mass ratio of 8:1:1, the hard carbon negative electrode material of the sodium ion battery, the conductive carbon black, and the binder (polyvinylidene fluoride) were taken into a small beaker, and an appropriate amount of nitrogen methyl pyrrolidone was added to stir and mix, and then aluminum foil or as a current collector was used, and then coated with a coating machine, and placed in a vacuum drying oven for drying (vacuuming and the temperature was 80°C, and the insulation time was 10h). The pole piece with a diameter of 10mm was cut out with a cutting machine; the button battery was assembled in a glove box with an oxygen / water content of less than 0.01ppm, and the assembly order was positive electrode shell, pole piece, diaphragm, sodium sheet, gasket, negative electrode shell, where the diaphragm material was glass fiber, and the electrolyte was 1mol / L sodium perchlorate dimethyl ether solution. The button battery was assembled with sodium metal as the counter electrode, and the cycle performance and rate performance of the installed pole piece were tested using the Blue Electric system.
[0080] Example 2
[0081] This embodiment provides a method for preparing a sodium ion battery hard carbon negative electrode material and a sodium ion battery electrode, which is similar to Embodiment 1, except that in step S6, the final carbonization temperature is 1200°C.
[0082] Example 3
[0083] This embodiment provides a method for preparing a sodium ion battery hard carbon negative electrode material and a sodium ion battery electrode, which is similar to Embodiment 1, except that in step S6, the final carbonization temperature is 1400°C.
[0084] Comparative Example 1
[0085] This comparative example provides a method for preparing a sodium ion battery hard carbon negative electrode material and a sodium ion battery electrode, which is similar to Example 1, except that the F doping in step S5 is not performed.
[0086] Comparative Example 2
[0087] This comparative example provides a method for preparing a sodium ion battery hard carbon negative electrode material and a sodium ion battery electrode, which is similar to Example 1, except that: the pore-forming agent in step S4 is not used to form pores, and step S5 is directly performed, followed by high-temperature carbonization.
[0088] Comparative Example 3
[0089] This comparative example provides a sodium ion battery electrode and a method for preparing a sodium ion battery electrode, which is similar to Example 1, except that the carbonized material prepared in step S1 is not subjected to acid-base treatment and pore-forming agent pore-forming, but is first pre-carbonized at a low temperature of 300°C and then carbonized at a high temperature of 1300°C.
[0090] Comparative Example 4
[0091] This comparative example provides a method for preparing a sodium ion battery hard carbon negative electrode material and a sodium ion battery electrode, which is similar to Example 1, except that in step S6, the final carbonization temperature is 1100°C.
[0092] Comparative Example 5
[0093] This comparative example provides a method for preparing a sodium ion battery hard carbon negative electrode material and a sodium ion battery electrode, which is similar to Example 1, except that in step S6, the final carbonization temperature is 1500°C.
[0094] Comparative Example 6
[0095] This comparative example provides a method for preparing a sodium ion battery hard carbon negative electrode material and a sodium ion battery electrode, which is similar to Example 1, except that the biomass hard carbon material silkworm litter in step S1 is replaced with bran.
[0096] Comparative Example 7
[0097] This comparative example provides a method for preparing a sodium ion battery hard carbon negative electrode material and a sodium ion battery electrode, which is similar to Example 1, except that in the method for preparing the sodium ion battery electrode, the mass ratio of the sodium ion battery hard carbon negative electrode material: conductive agent: binder is 9:0.5:0.5.
[0098] Electrochemical performance test
[0099] The battery was assembled in a glove box filled with argon. The counter electrode was the sodium ion battery electrode prepared in Example 1, the separator was glass fiber, and the electrolyte was 1M sodium perchlorate in ethylene glycol dimethyl ether solution (1M NaClO4in DME). The assembled button cell was subjected to the following electrochemical performance tests at 30°C and 0.01-2.5V.
[0100] 1. Charge and discharge cycle performance test
[0101] The button sodium ion batteries prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Examples 4-7 were respectively charged at a current density of 200 mAg -1 A long cycle test was carried out under Figures 1 to 7 shown.
[0102] in Figure 1 The long cycle performance diagram is obtained under the optimal experimental conditions (Example 1). The initial test conditions are 20 mA g -1 The current density was 50 mA g -1 5 cycles, 100mAg -1 Cycle 5 times, and finally keep 200mAg -1 The current density was tested. Figures 2 to 7 The test conditions are 20mAg -1 The current density was 50 mAg for 3 cycles. -1 Cycle 5 times, and finally maintain 100mAg -1 The current density was tested, and the specific capacity of Example 1 was 200mAg -1 The first cycle discharge capacity was 371.17 mAh g -1 , the charging capacity is 338.96mAh g -1 The first coulombic efficiency is 91.32%, which is better than the specific capacity of comparative examples 1, 2 and 4-7 (the first cycle charging specific capacity is: 278.6 mAh g -1 , 263.4mAh g -1 , 287.6mAh g -1 、291.2mA hg -1 、283.5mAhg -1 , 266.3mAh g -1 ), and the first coulombic efficiency (ICE) of Example 1 is also better than that of Comparative Example 1, Comparative Example 2 and Comparative Examples 4-7, and the capacity retention rate after 100 cycles is also the highest, indicating that the method used in the present invention exhibits higher coulombic efficiency and excellent long cycle performance in biomass hard carbon materials.
[0103] 2. Charge and discharge rate performance test
[0104] Figure 8 The hard carbon negative electrode material obtained in Example 1 is 20 mAg -1 , 50mAg -1 , 100mAg -1 , 200mAg -1 、500mAg -1 , 1000mA g -1and 2000mAg -1 Rate performance at current density of Fig. 9 The hard carbon negative electrode material obtained in Comparative Example 2 was -1 , 50mAg -1 , 100mAg -1 , 200mA g -1 , 500mA g -1 and 1000mA g -1 The rate performance at a current density of Figure 8 and Fig. 9 By comparison, it can be seen that the reversible capacity measured in Example 1 is significantly better than the material performance obtained in Comparative Example 2 without using the pore-forming agent to mix with the material, and at high current density, the specific capacity fluctuation of Example 1 is smaller, which shows that the treatment of Example 1 can effectively improve the specific capacity of the material at a larger current density, and the rate performance is more superior.
[0105] 3. XRD analysis
[0106] Fig.10 , 11 The XRD tests of the materials of Example 1 and Comparative Example 3 are respectively performed. Fig.10 It can be seen that the material contains many impurities without any treatment, which means that there are many impurities in the raw material, and the presence of these impurities will affect the electrochemical performance and stability of the material. After acid-base treatment and HF hydrothermal treatment, only two "small bulges" representing amorphous carbon are left, which are 23° and 42° respectively, and there are no other impurities, indicating that the method in Example 1 is very effective in treating impurities contained in biomass materials.
[0107] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a biomass hard carbon negative electrode material, characterized in that: The following steps are involved: (1) pretreating, crushing and pre-carbonizing the biomass raw material to obtain a pre-carbonized material; (2) mixing and stirring the pre-carbonized material obtained in step (1) with an acidic solution, washing and drying to obtain an acid-treated hard carbon material; (3) immersing the acid-treated hard carbon material obtained in step (2) in an alkaline solution, heating and stirring, washing and drying to obtain an alkali-treated hard carbon material; (4) mixing the alkali-treated hard carbon material obtained in step (3) with a pore-forming agent, ball milling, solid-liquid separation, and high-temperature carbonization and grinding of the obtained solid phase to obtain a powder sample; (5) Mixing the powder sample obtained in step (4) with hydrofluoric acid and subjecting it to hydrothermal treatment to obtain a biomass hard carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: In step (1), the pre-carbonization treatment conditions are: carbonization at 200°C-400°C for 1h-12h; And / or, the biomass raw material is silkworm litter.
3. The preparation method according to claim 1, characterized in that: In step (2), the acid in the acidic solution is one or more of hydrochloric acid, nitric acid and sulfuric acid; And / or, the concentration of the acidic solution is 0.1 mol / L-3 mol / L.
4. The preparation method according to claim 1, characterized in that: In step (3), the alkali in the alkaline solution is potassium hydroxide and / or sodium hydroxide; And / or, in step (3), the heating conditions are: heating at 60°C-90°C for 3h-8h.
5. The preparation method according to claim 1, characterized in that: In step (4), the pore-forming agent is zinc chloride and / or potassium hydroxide; And / or, the mass ratio of the alkali-treated hard carbon material to the pore-forming agent is 3:1-10:
1.
6. The preparation method according to claim 1, characterized in that: In step (4), the material ratio of the ball mill is 4-10:1; And / or, the rotation speed of the ball mill is 300r / min-600r / min; And / or, the ball milling time is 3h-8h.
7. The preparation method according to claim 1, characterized in that: In step (4), the high temperature carbonization temperature is 1200°C-1400°C; And / or, the heating rate of the high temperature carbonization is 2°C / min-10°C / min; And / or, the high temperature carbonization holding time is 2h-6h; And / or, the high temperature carbonization is carried out under an inert atmosphere; And / or, the conditions of the hydrothermal treatment are: 80°C-200°C for 10h-18h.
8. The biomass hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 7.
9. Application of the biomass hard carbon negative electrode material according to claim 8 in the field of energy storage.
10. A sodium ion battery, characterized in that: The biomass hard carbon negative electrode material according to claim 9 is used as the negative electrode material.
Citation Information
Patent Citations
Biomass-based doped hard carbon material and preparation method thereof
CN117585663A
New energy battery biomass hard carbon production process
CN118684210A
Cited By
Preparation method of bamboo-based hard carbon negative electrode material
CN122301176A
Composite carbon material, preparation method and application thereof, and alkali metal ion battery
CN122338027A